Torchbearers : Whitworth stories - Strauch, Elizabeth; Riddle, Julie; Wisenor, Tad (Whitworth University, 2014)
Across Whitworth's 125-year history, a host of torchbearers have dedicated themselves to living out and sustaining Whitworth's mission to equip graduates to "honor God, follow Christ, and serve humanity." Current students and alumni, transformed by Whitworth, go on to transform the people they meet and places they live. Faculty, staff, trustees and friends, through faith, commitment, leadership and vision, established Whitworth's foundation in 1890, developed the school into a thriving college, guided the institution through eras of challenge and change, and now shepherd Whitworth into a promising future. From the foreword.